Analisis Akuntansi Persediaan Barang Dagang Pada Toko Indomaret Basuki Rahmat Di Kota Jambi - Rita Mulyani; Mellya Embun Baining; Marissa Putriana (STEKOM PRESS, 2023)
This study aims to describe the recording and valuation of merchandise inventory at Indomaret Basuki Rahmat Jambi City based on Statement of Financial Accounting Standards (PSAK) Number 14 Concerning Inventory and find out the obstacles encountered in carrying out merchandise calculations at Indomaret Basuki Jambi City. This type of research used in this research is descriptive qualitative research. The data collection techniques used are observation, interviews, documents and informants. The research results showrecording and valuation of merchandise inventory at Indomaret Basuki Rahmat City of Jambi is carried out based on the Statement of Financial Accounting Standards (PSAK) Number 14 Concerning Inventory, namely by recording inventory, measuring inventory, costing inventory, recognizing expenses and disclosing inventory. Indomaret Basuki Jambi City uses the FIFO (First In First Out) inventory valuation method. Obstacles encountered in carrying out the calculation of merchandise at Indomaret Basuki Jambi City are calculation errors, layout of goods, supervision that is not optimal, employee negligence and communication, inventory does not match warehouse capacity, and lack of employee cooperation.